A developmental perspective on religious orientation dimensions - Kahoe, Richard D. (Journal of religion and health, 1981)
L.B. Brown's model of religious faith posits two bipolar religious orientations (intrinsic-extrinsic and autonomy-observance) that represent a two-dimensional space in which a religious believer can be located. This paper proposes a developmental sequence within Brown's model. The psychometric tradition of religious orientations is combined with a developmental tradition. The developmental process is consistent with models by A. Maslow, L. Kohlberg, J. Fowler, and J. Loevinger. Religious faith typically springs from extrinsic motivations. Most religious adherents achieve the next level, "observance," or identification with a religious community and its creeds. Some progress to intrinsic religiousness, and fewer attain religious autonomy.